Successful and unsuccessful transitions to the elite level: The youth national team pathways in Norwegian handball - Bjørndal, C. T.; Andersen, S. S.; Ronglan, L. T. (International Journal of Sports Science & Coaching, 2018)
The aim of this study was to explore successful and unsuccessful transitions in Norwegian handball from the youth player level to the adult elite level. The nine youth players in our strategic sample were interviewed in-depth about their experiences. Five of the nine athletes had established themselves successfully at the adult elite level; four had either quit or continued to play at a lower level during the previous season. The data were first inductively analysed before the theoretical analysis was conducted. This enabled us to develop a comprehensive understanding of each athlete`s developmental path and transitions and enabled a comparison between the different outcomes. The lifespan model was used a basis for understanding the individual pathways of development and the transitions made. The ecology of games framework was used to contextualise the individual processes within the particular organisational context of Norwegian handball. The results show how the application of the talent development model used in Norwegian handball is frequently experienced as one which is exhausting for athletes. For a significant number, it may lead to injuries or burnout. Further, our findings demonstrate that there is a thin line separating two different outcomes: (a) a dropout due to a loss of motivation and meaning and (b) a successful transition to the elite level. We discuss how the organisational context of Norwegian handball leads to unintended consequences, both positive and negative, for athletes. Incidents and decisions beyond an athlete`s immediate environment can facilitate or inhibit successful transitions to the elite level.